Fermented tea residue improved growth performance, liver antioxidant capacity, intestinal morphology and resistance to Aeromonas hydrophila infection in juvenile largemouth bass (Micropterus salmoides) - Jiang, Li; Zhou, Xinhong; Yu, Jing; Bao, Songsong; Li, Jin; Wu, Qiuhong; Wu, Mengjia; Wang, Yachao; Liu, Bo (Frontiers in Marine Science, 2022)
The study aimed to evaluate the effects of fermented tea leaf residue (TF) on growth performance, intestinal morphology, liver antioxidant capacity and Aeromonas hydrophila infection in juvenile Largemouth bass. Four trial diets T0 (basal diet) and T1, T2, and T3 (Add 2%, 4% and 6% of TF to the basal diet, respectively) were prepared for the experiment. The fish were randomly divided into 4 treatment groups with 3 replicates per treatment (20 fish/replicate) and rearing trials were conducted for 8 weeks. The results of the test showed that: 1) TF can significantly increase the weight gain rate and specific growth rate of juvenile largemouth bass compared with T0 (P < 0.01); 2) The intestinal villi of juvenile largemouth bass were longer and denser after feeding TF, and the height and width of intestinal villi were significantly higher than those of T0 (P < 0.01); 3) TF significantly increased the activities of SOD, GSH-PX and CAT in the liver of juvenile largemouth bass and decreased the MDA compared with those of T0 (P < 0.01); 4) Mortality occurred in all groups of largemouth bass after the injection of A.hydrophila, but feeding TF reduced the cumulative mortality compared with T0 (P < 0.05)；5) Compared with T0, the relative mRNA expression of intestinal pro-inflammatory factors IL-1β, IL-15, IL-8 and TNF-α decreased significantly and the relative mRNA expression of anti-inflammatory factors IL-10 and TGF-β1 increased significantly after feeding TF for juvenile largemouth bass (P < 0.01). In summary, it can be seen that a 2% TF addition amount can improve the liver antioxidant capacity of juvenile largemouth bass, enhance the resistance to A.hydrophila and increase the growth of largemouth bass.